Does an acute pain service improve the perception of postoperative pain management in patients undergoing lower limb surgery? A prospective controlled non-randomized study - Sukanya Mitra; Kompal Jain; Jasveer Singh; Swati Jindal; Puja Saxena; Manpreet Singh; Richa Saroa; Vanita Ahuja; Jannat Kang; Sudhir Garg (Wolters Kluwer Medknow Publications, 2020)
Background and Aim: An acute pain service (APS) has been running in our institute since April 2013 and is managed by the Department of Anesthesia and Intensive Care. However, it is not clear to what extent the patients feel benefited from the APS. The aim of the study was to compare the perception of postoperative pain management in patients receiving care under APS with those receiving routine postoperative pain relief following lower limb surgery. Material and Methods: This was a prospective, hospital-based, controlled non-randomized study. American Society of Anesthesiologists (ASA) grades I-III patients with age 18-75 years undergoing lower limb orthopedic surgery were prospectively recruited into APS (index group) or routine postoperative care (control group) (n = 55 each). Postoperatively, American Pain Society Patient Outcome Questionnaire-Revised (APS-POQ-R) and Short Form (SF-12) were used to evaluate the outcome of postoperative pain management at 24 h and health-related quality of life after 4 weeks respectively. Results: Both groups were comparable in terms of demographic data. Patients in the index group had statistically significant better perception of care than the control group. Index group scored significantly higher than control group on median patient satisfaction score (9; interquartile range [IQR] [7-10] vs. 5 [3-6]; P < 0.001). In index group, there was significant reduction of worst pain in first 24 h along with decreased frequency of severe pain. Conclusion: Implementation of acute pain service plays an important role in improving the quality of postoperative pain relief, perception of care, and patient satisfaction.